Risk Factors for Chronic Pain in Women: The Role of Violence Exposure in a Case–Control Study - Allison Uvelli; Erica Pugliese; Fabio Ferretti (Life)
Background: Chronic pain is an unpleasant sensory and emotional experience that greatly affects functioning and well-being. Studies link chronic pain and violence against women, with an odds ratio of 2.08 and a 26% prevalence rate. The bio-psycho-social consequences reduce quality of life and cause disability. Despite extensive research, the etiology remains unclear. This study investigates the bio-psycho-social risk factors of chronic pain in women, both victims and non-victims of violence. Methods: A case–control study (December 2023–June 2024) used odds ratios and Fisher’s exact test to explore risk factors associated with chronic pain. Univariate logistic regressions identified significant predictors. Results: The study included 170 women (68 victims), half with chronic pain. Nine risk factors were specific to victims (three biological, six psycho-social), four to non-victims (two biological, two psycho-social), and twenty-three to all women (five biological, eighteen psycho-social). A four-factor model best explained risk in victims and all women, while a two-factor model fit non-victims. Conclusions: The bio-psycho-social model of chronic pain is supported, identifying specific risk factors. These findings can aid anti-violence and healthcare professionals in screening and early intervention.